Piles In Peat Under Artesian Pressure: A Case Study ? Synopsis - K. Y. C. Chung (Deep Foundations Institute, 2010)
A case study on foundation engineering through organic soils is presented. Located along the west shore of the Hudson River, site soils consist of random brick fill over a thick layer of peat and organic silts or clays. The organic layer is underlain by medium dense to dense sand with varying amounts of silt. Strong artesian pressures were measured in the sand. A pile foundation system was selected to support all structures. To avoid periodic flooding, new fill must be placed on the existing fill. Large total and differential settlements will occur due to consolidation and secondary compression of the organic soils. This settlement will reduce the allowable pile capacity due to the large negative skin friction in the organic layer; and will necessitate long-term maintenance of the final grade elevation. Pile load tests were performed to determine the allowable compression and uplift capacities, long-term capacities and pile driving criteria.